The Qualities of Reconstructed Liquid Egg White Utilizing Plant-based Proteins - Inkorn, Nattapassorn; Kaewsritong, Jiraphat; Srikaeo, Khongsak (Journal of Food Health and Bioenvironmental Science, 2025)
This study aimed to evaluate the properties of reconstructed liquid egg white formulated with plant proteins isolated from various sources (soy, pea, rice, and mung bean) and supplemented with carrageenan at concentrations ranging from 0% to 5%. The reconstructed products were prepared by mixing all ingredients, molding, and steaming to achieve the desired structure. Key quality attributes, including appearance, pH, color, water activity (aw), texture, suitability for dysphagia diets, and sensory characteristics, were analyzed. The reconstructed liquid egg white with plant proteins exhibited an acceptable appearance and texture, resembling meat analogues. The addition of carrageenan significantly influenced the textural properties, with 3% carrageenan yielding the highest values for hardness, springiness, gumminess, and chewiness—characteristics desirable for the final product. The fork pressure test confirmed that the products met the criteria for dysphagia diets. However, sensory evaluation revealed relatively low acceptance scores across most attributes, with maximum scores below 7 ("like moderately"). Despite this, the products contained a high protein content, ranging from 19% to 22% on a wet basis. This study demonstrates a straightforward approach to formulating texturized foods using egg white and plant proteins, both high-quality protein sources, offering potential applications in specialized diets and protein-enriched food products.